Narrative Review: The Effect of Inulin on the Growth of Bifidobacterium in the Human Intestine - Nurzamani, Salsabila; Kasasiah, Ahsanal (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Bifidobacterium is an important probiotic bacterium that plays a key role in maintaining gut microbiota balance and supporting digestive health. Inulin has been widely studied as a prebiotic due to its ability to stimulate the growth of Bifidobacterium through fermentation in the colon. This study aims to summarize recent scientific evidence regarding the effects of inulin supplementation on the increase of Bifidobacterium populations in humans. This study aims to summarize recent scientific evidence regarding the effects of inulin supplementation on the increase of Bifidobacterium populations in humans. This article was prepared using a narrative review method based on literature searches conducted in PubMed, ScienceDirect, ClinicalKey, and Google Scholar. A total of nine original research articles that directly reported the effects of inulin supplementation were included. The findings consistently show that inulin increases the abundance of Bifidobacterium, improves gut microbiota balance, and enhances the production of short-chain fatty acids (SCFAs) such as acetate, butyrate, and propionate. These changes are also associated with improvements in metabolic markers among several populations, including obese children, prediabetic patients, and individuals with PCOS. Overall, inulin demonstrates strong bifidogenic effects, although individual responses may vary depending on dosage, duration of intervention, and physiological conditions.